Variation and correlation in the timing of breeding of North Atlantic seabirds across multiple scales - Keogan, Katharine; Daunt, Francis; Wanless, Sarah; Phillips, Richard; Alvarez, David; Anker-Nilssen, Tycho; Barrett, Robert; Bech, Claus; Becker, Peter; Berglund, Per‐arvid; Bouwhuis, Sandra; Burr, Zofia; et al. (Journal of Animal Ecology, 2022)
International audience 1. Timing of breeding, an important driver of fitness in many populations, is widely studied in the context of global change, yet despite considerable efforts to identify environmental drivers of seabird nesting phenology, for most populations we lack evidence of strong drivers. Here we adopt an alternative approach, examining the degree to which different populations positively covary in their annual phenology to infer whether phenological responses to environmental drivers are likely to be (i) shared across species at a range of spatial scales, (ii) shared across populations of a species, or (iii) idiosyncratic to populations. 2. We combined 51 long‐term datasets on breeding phenology spanning 50 years from nine seabird species across 29 North Atlantic sites and examined the extent to which different populations share early versus late breeding seasons depending on a hierarchy of spatial scales comprising breeding site, small‐scale region, large‐scale region and the whole North Atlantic. 3. In about a third of cases we found laying dates of populations of different species sharing the same breeding site or small‐scale breeding region were positively correlated, which is consistent with the hypothesis that they share phenological responses to the same environmental conditions. In comparison we found no evidence for positive phenological covariation among populations across species aggregated at larger spatial scales. 4. In general we found little evidence for positive phenological covariation between populations of a single species, and in many instances the inter‐year variation specific to a population was substantial, consistent with each population responding idiosyncratically to local environmental conditions. Black‐legged kittiwake (Rissa tridactyla) was the exception, with populations exhibiting positive covariation in laying dates that decayed with the distance between breeding sites, suggesting that populations may be responding to a similar driver. 5. Our approach sheds light ...